The Effect of E-Service Quality on E-Customer Loyalty with E-WOM and Brand Image as Mediating Variables (Study on Shopee Food Consumers in Malang City) - Al Mukaromah Dewi Puspita; Sudarmiatin; Titis Shinta Dhewi (CV. AFDIFAL MAJU BERKAH, 2022)
The development of the world of business and trade cannot be separated from technological advances. Applications for ordering food and beverages facilitate consumers to order online by using smartphone when they do not have much time to come directly to the store (offline). The aim of this study is that to find out Shopee Food Indonesia, which will be a strong competitor for other food and beverage service companies. This study was a quantitative research using SPSS 25. The populations in this study were consumers who used Shopee Food with a sample of 280 respondents. Meanwhile, the analysis technique used path analysis and Sobel test. The results of the description analysis of the E-Service Quality variable on E-Customer Loyalty with E-WOM and Brand Image resulted in a value in the very good category. The results of this study show that (1) E-Service Quality is proven to have a direct positive and significant effect on E-WOM. (2) E-Service Quality is proven to have a direct positive and significant effect on Brand Image. (3) E-Service Quality is proven to have a direct positive and significant effect on E-Customer Loyalty. (4) E-Service Quality is proven to have a direct positive and significant effect on E-Customer Loyalty. (5) E-Service Quality is proven to have a direct positive and significant effect on E-Customer Loyalty. (6) E-WOM is able to mediate the relationship between the influence of E-Service Quality on E-Customer Loyalty. (7) Brand Image is able to mediate the relationship between the influence of E-Service Quality on E-Customer Loyalty. The suggestions for Shopee Food Indonesia is that it should improve the quality of the system, merchants and employees; besides, stay active on all social media such as Instagram, Facebook, Twitter, etc. It is expected that with social media, it can provide information between companies and consumers.